(untitled) (Research in Agriculture Livestock and Fisheries, 2016)
A study was conducted to investigate the effect of some postharvest treatments on shelf life and quality of mango. Experiment was conducted at the BAU Germplasm centre, Department of Horticulture, Bangladesh Agricultural University, Mymensingh during May to July, 2013. Two treatments viz. Aloe vera and Chitosan solution were used for this study. The experiment was laid out in Completely Randomized Design (CRD) to observe the post-harvest performance of mango with three replications. The fruits were divided into three grades eg. large, medium and small for the convenience of the experiment. In each group mango were treated with Aloe vera gel and Chitosan solution in three different concentrations of 0.5%, 1% and 1.5%. Amropali cultivar had the highest shelf life (7days) at 1.5% Aloe vera gel treatment to the large size mangoes at room temperature compare to other sizes and treatments. Nearly, similar effect was obtained from 1.5% Aloe vera gel to the medium size fruits than other treatments. 1.5% Chitosan showed the second best result in case of shelf life extension followed by 1% Chitosan solution. Res. Agric., Livest. Fish.3(2): 279-286, August 2016